"Asking Is Never Bad, I Would Venture on That": Patients' Perspectives on Routine Pain Screening in VA Primary Care. Issue 10 (6th March 2020) - Giannitrapani, Karleen F; Haverfield, Marie C; Lo, Natalie K; McCaa, Matthew D; Timko, Christine; Dobscha, Steven K; Kerns, Robert D; Lorenz, Karl A
Abstract: Objective: Screening for pain in routine care is one of the efforts that the Veterans Health Administration has adopted in its national pain management strategy. We aimed to understand patients' perspectives and preferences about the experience of being screened for pain in primary care. Design: Semistructured interviews captured patient perceptions and preferences of pain screening, assessment, and management. Subjects: We completed interviews with 36 patients: 29 males and seven females ranging in age from 28 to 94 years from three geographically distinct VA health care systems. Methods: We evaluated transcripts using constant comparison and identified emergent themes. Results: Theme 1: Pain screening can "determine the tone of the examination"; Theme 2: Screening can initiate communication about pain; Theme 3: Screening can facilitate patient recall and reflection; Theme 4: Screening for pain may help identify under-reported psychological pain, mental distress, and suicidality; Theme 5: Patient recommendations about how to improve screening for pain. Conclusion: Our results indicate that patients perceive meaningful, positive impacts of routine pain screening that as yet have not been considered in the literature. Specifically, screening for pain may help capture mental health concerns that may otherwise not emerge.